Strategies to strengthen students' digital literacy through contextual learning in Pancasila Education - Herhana, Nodi; Rusnaini, Rusnaini; Nuryadi, Muh. Hendri (International Journal Labs, 2024)
This study aims to explore strategies for strengthening students' digital literacy through contextual learning in Pancasila Education at SMKN 4 Kendal, by describing strategies and identifying related obstacles and solutions. The method used is qualitative with a case study approach, relying on interviews with eight grade XI Culinary 1 students and one Pancasila Education teacher, as well as documentation and observation. Data validity is tested through triangulation, and data analysis involves collecting, condensing, presenting, and inferring data. The results showed that digital literacy can be strengthened through contextual learning with three main steps: strategy design, application of learning, as well as overcoming obstacles and finding solutions. Barriers for students are divided into in-class (such as lack of quota, inactive members, and drowsiness) and outside the classroom (lack of discipline, long distances, and bad weather). Barriers for teachers include long module preparation, lack of student focus, and difficulties in exploratory mentoring. In-class solutions include buying quota before school, approaching less-active friends, and going to bed early. Solutions outside the classroom include making time agreements, determining gathering points, and monitoring the weather. For teachers, the solution is to discuss with colleagues, provide ice breaking, and accompany via WhatsApp groups.